The Mediterranean deep-water kelp Laminaria rodriguezii is an endangered species in the Adriatic Sea - Ante Žuljević; Akira F. Peters; Vedran Nikolić; Boris Antolić; Marija Despalatović; Ivan Cvitković; Igor Isajlović; Hrvoje Mihanović; Slavica Matijević; Dawn M. Shewring; Simonepietro Canese; Christos Katsaros; et al. (Marine Biology, 2016)

Effects of high temperature on the ultrastructure and microtubule organization of interphase and dividing cells of the seagrass Cymodocea nodosa - M. Koutalianou; S. Orfanidis; C. Katsaros (Protoplasma, 2016)

Seaweeds of the Greek coasts. II. Ulvophyceae - K. TSIAMIS; P. PANAYOTIDIS; A. ECONOMOU-AMILLI; C. KATSAROS (Mediterranean Marine Science, 2014)
An updated checklist of the green seaweeds (Ulvophyceae) of the Greek coasts is provided, based on both literature records and new collections. The total number of species and infraspecific taxa currently accepted is 95. The occurrence of each taxon in the North Aegean, South Aegean and Ionian Seas is given. In addition, 12 taxa pending confirmation of their presence, 9 excludenda and 14 inquirenda are briefly discussed.

Seaweeds of the Greek coasts. I. Phaeophyceae - K. TSIAMIS; P. PANAYOTIDIS; A. ECONOMOU-AMILLI; C. KATSAROS (Mediterranean Marine Science, 2013)
An updated checklist of the brown seaweeds (Phaeophyceae) of Greece is provided, based on both literature records and new collections. The total number of species and infraspecific taxa currently accepted is 107. The occurrence of each taxon in the North Aegean, South Aegean and Ionian Seas is given. In addition, 17 taxa pending confirmation of their presence, 11 excludenda and 8 inquirenda are briefly discussed.

Seaweeds of the Greek coasts. I. Phaeophyceae - K. TSIAMIS; P. PANAYOTIDIS; A. ECONOMOU-AMILLI; C. KATSAROS (Mediterranean Marine Science, 2013)

Notes on new records of red algae (Ceramiales, Rhodophyta) from the Aegean Sea (Greece, eastern Mediterranean) - K. Tsiamis; B. Montesanto; P Panayotidis; C. Katsaros (Plant Biosystems, 2011)

Updated records and range expansion of alien marine macrophytes in Greece (2009) - K. TSIAMIS; B. MONTESANTO; P. PANAYOTIDIS; C. KATSAROS; M. VERLAQUE (Mediterranean Marine Science, 2010)
In the present study the list of alien marine macrophytes already recorded on Greek coasts has been revised in the light of recent studies and new observations. In comparison to 2008, the total number consists of 32 taxa, and the classification as established, casual and debatable species has been modified, with a total of 14, 5 and 13 species respectively. An interesting increase in established species from 9 taxa in 2008 to 14 taxa in 2009 is noted. With 23 taxa listed, Rhodobionta is the best represented group, followed by Chlorobionta (4 taxa) and Chromobionta (4 taxa), while seagrasses (Streptobionta) are represented by only one species. Several new records, one new entry and two putative additions are considered here, while two other taxa previously assumed introduced are excluded from the list of aliens.

A unique pattern of F-actin organization supports cytokinesis in vacuolated cells of Macrocystis pyrifera (Phaeophyceae) gametophytes - V. Varvarigos; B. Galatis; C. Katsaros (Protoplasma, 2005)

Virus assembly inHincksia hincksiae (Ectocarpales, Phaeophyceae) An electron and fluorescence microscopic study - Susanne Wolf; I. Maier; C. Katsaros; D. G. Mller (Protoplasma, 1998)

Centrosome and microtubule dynamics in apical cells ofSphacelaria rigidula (Phaeophyceae) treated with nocodazole - D. Karyophyllis; B. Galatis; C. Katsaros (Protoplasma, 1997)